(untitled) (مجلة دراسات إقلیمیة, 2026)
Research Idea: This study examines the relationship between Iran and the Russia–Ukraine War during the period 2022–2024. It proceeds from the premise that the conflict has revealed profound shifts in the international balance of power, generated new alliances, and reshaped the global geopolitical landscape, making the positions of regional states a key indicator of their strategic orientations and interests. Objective: The study seeks to clarify Iran’s stance toward the war, identify the forms and extent of support provided by Tehran to Moscow, and assess the implications of this support for both the course of the conflict and the development of bilateral relations. Methodology: The study employs two complementary approaches: the historical method to trace the evolution of Iranian–Russian relations and their underlying dynamics, and the analytical method to interpret relevant policies and positions and assess their broader implications. Results: The findings indicate that Iranian support for Russia extended beyond the political and diplomatic spheres to include military and economic dimensions, including the sharing of expertise in circumventing Western sanctions. This contributed to strengthening Russia’s position in the war and consolidating the strategic partnership between the two countries, while exposing Iran to additional Western sanctions. Conclusion: The study concludes that the Russia–Ukraine War was not merely a bilateral conflict between neighboring states, but also an arena of competition between two rival international blocs: one led by the United States and its Western allies, and the other headed by Russia with the support of China, Iran, and North Korea. Within this context, Iran assumed a pivotal role that it embraced with strategic calculation and deliberate intent.